2018
DOI: 10.1093/applin/amy055
|View full text |Cite
|
Sign up to set email alerts
|

Change in Metaphorical Framing: Metaphors of TRade in 225 Years of State of the Union Addresses (1790–2014)

Abstract: The literature provides diverging perspectives on the universality and stability of economic metaphors over time. This article contains a diachronic analysis of economic metaphors describing trade in a corpus of 225 years of US State of the Union addresses (1790–2014). We focused on two types of change: (i) replacement of a source domain by another domain and (ii) change in mapping within a source domain. In our corpus, five source domains of trade were predominant: (i) PhysicalObject, (ii) Building, (iii) Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Undeniably, the growth of academic papers on CM has contributed to the advancement of CM research. Numerous scholars have conducted a significant amount of research into CM from various perspectives, such as psycholinguistic metaphor research (Murphy, 1996;Gibbs, 2013;Qiu et al, 2022); deliberate metaphors and embodied simulation research (Gibbs, 2006;Cuccio and Steen, 2019;Cuccio et al, 2022); conceptual conflicts in metaphors and translation (Prandi, 2017;Rizzato, 2021Rizzato, , 2022; corpus-based metaphor research (Sinclair, 1991;Charteris-Black, 2000Semino, 2002;Deignan and Potter, 2004;Allen, 2006;Fabiszak, 2007;Tissari, 2010;Shutova et al, 2013;Burgers and Ahrens, 2018;Zhao and Zhou, 2019;Zhao et al, , 2020Silvestre-López, 2020;Bosman and Taljard, 2021;Kazemian and Hatamzadeh, 2022), critical metaphors in discourse analysis (Charteris-Black, 2004;Ferrari, 2007;Musolff, 2012) and metaphors in classroom teaching (Thomas and McRobbie, 2001;Andreou and Galantomos, 2008). There is also increasing research on various reviews of CM research (e.g., Allahmoradi, 2018;Holyoak and Stamenkovic, 2018;Bundgaard, 2019;Gandolfo, 2019;Tohidian and Rahimian, 2019;Kövecses, 2020;Bearman et al, 2021;Jensen et al, 2021;Abdul et al, 2022).…”
Section: Conceptual Metaphor Researchmentioning
confidence: 99%
“…Undeniably, the growth of academic papers on CM has contributed to the advancement of CM research. Numerous scholars have conducted a significant amount of research into CM from various perspectives, such as psycholinguistic metaphor research (Murphy, 1996;Gibbs, 2013;Qiu et al, 2022); deliberate metaphors and embodied simulation research (Gibbs, 2006;Cuccio and Steen, 2019;Cuccio et al, 2022); conceptual conflicts in metaphors and translation (Prandi, 2017;Rizzato, 2021Rizzato, , 2022; corpus-based metaphor research (Sinclair, 1991;Charteris-Black, 2000Semino, 2002;Deignan and Potter, 2004;Allen, 2006;Fabiszak, 2007;Tissari, 2010;Shutova et al, 2013;Burgers and Ahrens, 2018;Zhao and Zhou, 2019;Zhao et al, , 2020Silvestre-López, 2020;Bosman and Taljard, 2021;Kazemian and Hatamzadeh, 2022), critical metaphors in discourse analysis (Charteris-Black, 2004;Ferrari, 2007;Musolff, 2012) and metaphors in classroom teaching (Thomas and McRobbie, 2001;Andreou and Galantomos, 2008). There is also increasing research on various reviews of CM research (e.g., Allahmoradi, 2018;Holyoak and Stamenkovic, 2018;Bundgaard, 2019;Gandolfo, 2019;Tohidian and Rahimian, 2019;Kövecses, 2020;Bearman et al, 2021;Jensen et al, 2021;Abdul et al, 2022).…”
Section: Conceptual Metaphor Researchmentioning
confidence: 99%
“…Specifically, fundamental change is often indicated by the association between time and the use of a source domain. For instance, relatively little fundamental change was found in Burgers and Ahrens’ (2020) examination of diachronic change of trade metaphors in the State of the Union addresses delivered by the US Presidents over 225 years. In addition, free economy metaphors did not go through fundamental change in political discourse of Hong Kong, China over 20 years (Zeng et al, 2021).…”
Section: Research Backgroundmentioning
confidence: 99%
“…While most extant literature focuses on the analysis of the conceptual levels in the metaphors, diachronic variations in metaphorical framing have also received much attention together with quantitative analyses (e.g., Burgers 2016, Burgers & Ahrens 2020, Zeng, Burgers & Ahrens 2021. As pointed out by Musolff (2014: 58), "the cognitive approach on its own thus seems unable to provide a comprehensive model of diachronic meaning change", and he suggested that to account for the dissemination and entrenchment of metaphors, the discourse-historical approach (DHA) may be the most promising model as it integrates linguistic, social, and historical aspects of language (cf.…”
Section: Metaphors and Ideologies In Political Discoursementioning
confidence: 99%